2022
DOI: 10.56457/jimk.v10i2.298
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Service Quality and Current Account Customer Trust on the Decision to Save Funds at PT. Bank Central Asia Tbk Bekasi Main Branch Office

Abstract: The decision to save funds is often influenced by a variety of factors, including an individual's financial goals, income, expenses, and overall financial health. Service quality and customer trust in a bank's current account may also play a role in an individual's decision to save funds  The research method used in this study uses quantitative methods or often called traditional methods, because this method has been used for a long time so that it has become a tradition for research. The result is Quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…So it can be concluded that the hypothesis proposed is "customer engagement affects behavioural intention to use Traveloka Paylater" accepted or customer engagement has positive and significant effect on behavioural intention to use Traveloka Paylater. This is in line with research conducted by Mutaufiq et al (2022) which states that customer engagement has a positive and significant effect on customer interest in using (behavioural intention to use) BCA products with a significance value is 0.000 or < 0.05.…”
Section: Discussionsupporting
confidence: 91%
“…So it can be concluded that the hypothesis proposed is "customer engagement affects behavioural intention to use Traveloka Paylater" accepted or customer engagement has positive and significant effect on behavioural intention to use Traveloka Paylater. This is in line with research conducted by Mutaufiq et al (2022) which states that customer engagement has a positive and significant effect on customer interest in using (behavioural intention to use) BCA products with a significance value is 0.000 or < 0.05.…”
Section: Discussionsupporting
confidence: 91%